A sub-1V high PSRR OpAmp based β-multiplier CMOS bandgap voltage reference with resistive division - Anass SLAMTI; Youness MEHDAOUI; Driss CHENOUNI; Zakia LAKHLIAI (Institute of Advanced Engineering and Science, 2019)
A sub-1V opamp based β-multiplier CMOS bandgap voltage reference (BGVR) with high power supply rejection ratio (PSRR) and low temperature coefficient (TC) is proposed in this paper. A current mode regulator scheme is inserted to isolate the supply voltage of the operational amplifier (opamp) and the supply voltage of the BGVR core from the supply voltage source in order to reduce ripple sensitivity and to achieve a high PSRR. The proposed circuit is designed and simulated in 0.18-μm standard CMOS technology. The proposed voltage reference delivers an output voltage of 634.6mV at 27°C. Tthe measurement temperature coefficient is 22,3ppm/°C over temperature range -40°C to 140°C, power supply rejection ratio is -93dB at 10kHz and -71dB at 1MHz and a line regulation of 104μV/V is achieved over supply voltage range 1.2V to 1.8V. The layout area of the proposed circuit is 0.0337mm2. The proposed sub-1V bandgap voltage reference can be used as an internal voltage reference in low power LDO regulators and switching regulators.